Analisis Desain Pembelajaran Al-Qur'an Visual untuk Anak Autis di SLB Riverkids Malang - Sabiqun Khoirot; Khozin Khozin; Fahrudin Mukhlis (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Students of Riverkids Special School Malang have their own uniqueness in studying. They have different learning styles from other regular school students. The learning style of Autistic children is dominantly by memorizing information as it is (rote learner), and autistic students can even understand faster when they are provided with pictures to help them understand the information (visual learner). This study aims to investigate what media the autistic students used to learn how to read Quran at Riverkids Autism Special Schools Malang so they could recite Quran fluently. The study was conducted using three kinds of instruments: interviews, observation, and learning supporting documents. The researcher applied qualitative approach with the type of field research. Triangulation technique was used for data validation testing, which was using RPP (Lesson Plan) for observation, and then triangulation was used to obtain data from the interviews through the main questions asked to the headmaster, subject teachers, and students. The results of the study indicated that Quran learning at Riverkids Autism Special Schools Malang applied visual-based media. The Quran learning process included four stages: first, determining the materials and objectives based on independent curriculum; second, teaching aids adjustment; third, conditioning the class; forth, implementation of learning process.